2014
DOI: 10.3109/02713683.2014.957326
|View full text |Cite
|
Sign up to set email alerts
|

The Peterborough Scheme for Community Specialist Optometrists in Glaucoma: Results of 4 Years of a Two-Tiered Community-Based Assessment and Follow-up Service

Abstract: The SOG scheme demonstrates acceptable levels of accuracy between SOG and glaucoma consultant. This scheme allows many stable low-risk patients to remain out of hospital eye department outpatient clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 26 publications
(28 reference statements)
1
32
1
Order By: Relevance
“…The present study identified a potential clinical pathway for patients with suspected angle closure spectrum disease, where the majority of patients do not require onward ophthalmological assessment. The overall proportion of all patients who could be discharged back into the community for ongoing optometric care (20.1 per cent) was similar to some previous reports and was lower than others . Specifically with regard to patients referred for angle assessment, gonioscopic findings were not once noted in the referral letter, indicating a gap in current community optometry that is addressed in the present model.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The present study identified a potential clinical pathway for patients with suspected angle closure spectrum disease, where the majority of patients do not require onward ophthalmological assessment. The overall proportion of all patients who could be discharged back into the community for ongoing optometric care (20.1 per cent) was similar to some previous reports and was lower than others . Specifically with regard to patients referred for angle assessment, gonioscopic findings were not once noted in the referral letter, indicating a gap in current community optometry that is addressed in the present model.…”
Section: Discussionsupporting
confidence: 79%
“…The overall proportion of all patients who could be discharged back into the community for ongoing optometric care (20.1 per cent) was similar to some previous reports 6,11,24 and was lower than others. 7,[25][26][27] Specifically with regard to patients referred for angle assessment, gonioscopic findings were not once noted in the referral letter, indicating a gap in current community optometry that is addressed in the present model. Notably, although gonioscopy is a current graduate level clinical competency in optometry in Australia 28 and is one of the clinical tests expected to be performed in the comprehensive assessment of glaucoma, its use is not widespread in community practice.…”
Section: Discussionmentioning
confidence: 81%
“…EOS for community monitoring of patients with stable glaucoma or OHT have been evaluated . These services are protocol‐driven and generally overseen by the HES.…”
Section: Resultsmentioning
confidence: 99%
“…A RCT, comparing community monitoring of patients with stable glaucoma to routine care in the hospital glaucoma clinic, found community optometrists could take clinical measurements of comparable quality to usual care and there was no difference in patient outcomes between the two arms of the trial over a 2‐year period . Other studies, observational in design, concluded that with further glaucoma training, community optometrists are an acceptable alternative to hospital care for selected glaucoma patients and those at increased risk of developing glaucoma. In summary, evidence from glaucoma services provides strong support for Theory 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation